The Role of the "Taro Ada Taro Gau" Philosophy for Bugis Accountants - Abdul PATTAWE; Muhammad DIN; Jurana JURANA; Nurainun HABIBA (International Journal of Environmental, Sustainability and Social Science, 2025)
The philosophy of "taro ada taro gau" (determine words, determine actions) is part of Bugis culture. This philosophy is widely held by Bugis people in various professions. This also applies to Bugis accountants. This study aims to deeply understand and interpret the meaning of the "taro ada taro gau" philosophy for Bugis accountants in carrying out their profession. This study uses an interpretive paradigm with a transcendental phenomenological approach. Data collection was conducted through interviews, observation, and documentation to achieve the research objectives. The results of this study identified three research findings: 1) taro ada taro gau represents a consistent identity in interactions; 2) taro ada taro gau as self-reputation; 3) taro ada taro gau as a moral foundation.